Household food security in Iran: systematic review of Iranian articles - Alimoradi, zeinab; Kazemi, faridhe; Estaki, taraneh; Mirmiran, parvin (Advances in Nursing & Midwifery, 2015)
Introduction: Food and nutrition are basic needs of human society. Fulfilling this need lies in concept of food security. There are two main prerequisites for food security in any society: Ensure the availability and accessibility of food in society and ensure the ability of households to obtain food. Household food security means all family members have access to enough food for their minimum amount of necessary requirements. With a systematic review approach, this article wants to investigate the scales, prevalence, contributing factors and consequences of household food security in Iran. Methods and Materials: Proceedings of the Persian writers on household food security without limits of time, place and language publishing was searched thorough informative databases of PubMed, Elsevier , SID, Medlib, Magiran, Iranmedex, Irandoc, Google Scholar using "food security, food insecurity, associated factors, prevalence, causes, women, children and Iran" as search keywords. Findings: Six scales for assessing household food insecurity has been used in Iranian studies. According to various studies, regardless of the scale used, the prevalence of food insecurity was about 20 to 60%; and in female-headed households and low-income communities, 75 and 86% have been reported. Reduce variation in food consumption and intake of essential micronutrients, poor nutritional status of infants, inconsistent effects on body mass index and weight of children, adolescents, women and men were the studied consequences of food insecurity. Conclusion: Household food security is considered as an indicator of individual and family health which can be measured to help policy makers and other institutions to design, monitor and evaluate programs and interventions. At national and provincial levels, there are good policy and practices in this field .Due to nutritional transition, increased urbanization and demographic changes in Iran, investigating food security status at the individual and family level, influencing social and cultural factors, its consequences, Design, implement and evaluate proper interventions need further consideration by policy makers, government officials and experts in the country. Keywords: Household food security, prevalence, influencing factors, consequences, Iran.